Propositional density: cognitive impairment and aging - Harrag, Chaimae; Sabil, Abdelkader; Conceição, Manuel Célio; Radvansky, Gabriel A. (Frontiers in Psychology, 2024)
It is important to understand the relationship between cognitive abilities and language processing. Here, we explore a burgeoning area of research that harnesses semantic indices to predict cognitive impairment and track cognitive decline. One such index, propositional density, quantifies the information conveyed per language segment. Despite some variation stemming from methodological, sampling, and measurement differences, we suggest that propositional density has diagnostic and assessment value. This paper surveys existing studies that have used propositional density in the context of cognitive aging and impairment and offers some insights into the use of this index to highlight differences in cognition. We also suggest further explorations of basic research involving this concept, and some applications for assessing cognitive health.